Metal-ceramic resin-bonded fixed partial dentures after a mean observation time of 7.5 years - Handermann, Rebecca; Rammelsberg, Peter; Bömicke, Wolfgang (The international journal of prosthodontics, 2024)
Purpose: To generate data on the long-term survival of metal-ceramic resin-bonded fixed partial dentures (RBFPDs). Materials and Methods: A total of 89 patients received 94 RBFPDs, 5 of whom (women n = 1; men n = 4) received 2 RBFPDs each. All RBFPDs were fabricated as two-retainer end-abutment metal-ceramic restorations. Clinical follow-ups were performed 6 months after cementation and then annually thereafter. The mean observation time was 7.5 years. Cox regression was performed to test the effects of the variables: gender, location, arch, design, use of rubber dam, and adhesive luting system. Survival and success were calculated using Kaplan-Meier curves. As a secondary objective, patient and dentist satisfaction with the esthetics and function of the RBFPDs was evaluated. The significance level was set at α = .05 for all calculations. Results: Estimated Kaplan-Meier failure-free survival was 97.5% (standard error [SE] 1.7) after 5 years and 83.3% (SE 5.3) after 10 years. Calculated intervention-free survival (success) was 90.1% (SE 3.4) after 5 years and 65.5% (SE 6.7) after 10 years. Debonding-free survival was 92.6% (SE 2.9) after 5 years and 80.6% (SE 5.4) after 10 years. Cox regression revealed that none of the four tested variables had a significant effect on the incidence of complications in RBFPDs. Patient and dentist satisfaction with RBFPD esthetics and function was consistently high throughout the observation period. Conclusions: Within the limitations of an observational study, RBFPDs achieved clinically successful outcomes over a mean observational period of 7.5 years.